A study of some key problems of hall accelerator operation over the expended range of discharge voltage - Oghienko, S.A.; Oranskiy, A.I.; Belokon, V.I.; Bober, A. (Вопросы атомной науки и техники, 2007)
Hall accelerators (HA) (thruster) are effectively applied in space propulsion and as a source of ions for controlled fusion and another programs. For HA modernization (by expansion of a discharge voltage range) some key problems have been studied: the determination of potential drop in various zones of discharge interval; the calculation of HA integrated characteristics; the determination of influence of low-frequency azimuthally plasma heterogeneity on electron movement.